Evaluation of kidney function and damage in patients with hemophilia B—insights from the B-Natural study - Astermark, Jan; LeBeau, Petra; Christensson, Anders; Lethagen, Stefan; Berntorp, Erik; Shapiro, Amy D. (Research and practice in thrombosis and haemostasis, 2025)
Background: Patients with hemophilia are reported to have a high prevalence of established and potential risk factors for kidney dysfunction and damage. However, comprehensive studies specifically evaluating kidney function in hemophilia, particularly hemophilia B (HB), are limited, with most research focusing on hemophilia A. Objectives: This study aimed to assess markers of glomerular filtration, damage, and tubular function in patients with HB enrolled in the B-Natural study. Methods: Kidney function and damage was evaluated using estimated glomerular filtration rate (eGFR), urine albumin/creatinine ratio, urinary immunoglobulin/creatinine ratio, and protein HC. Correlations with patient characteristics, treatment regimes, and comorbidities were analyzed. Results: The cohort consisted of 209 patients with HB, with 32% having severe, 51% moderate, and 17% mild disease. The median age was 13 years (IQR, 9-22 years; range, 1-73 years). The mean eGFR across the cohort was 107 mL/min/1.73 m2 (range, 13-183 mL/min/1.73 m2). Older age, higher body mass index, a history of kidney disease, diabetes, hypertension, and Asian ethnicity were significantly associated with lower eGFR. Patients with severe HB (factor IX < 1%), and/or a history of inhibitors exhibited a wider range of eGFR values. Only a small proportion of patients showed glomerular damage and tubular dysfunction. Regular prophylactic treatment with factor concentrates had no apparent impact on kidney function or kidney disease markers. Conclusion: Our findings suggest that patients with HB and no inhibitors do not have an increased risk of kidney dysfunction or damage compared to persons without hemophilia. Age and hypertension were the primary risk factors, underscoring the importance of regular follow-ups.
Keywords: factor IX deficiency; hemophilia B; hypertension; kidney disease; renal insufficiency